Gender transformation through scaling in climate resilient agriculture: The experience of AICCRA - Huyer, Sophia; Obeng Adamaa, Faustina (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Gender transformation is about addressing structural inequalities that fundamentally alter the lives of women and men. In the context of scaling, it is about large scale changes or trends that address structural inequalities to work towards the individual empowerment of women and men, and greater equality. In this approach, gender-transformative research looks at root causes and process of inequalities with the objective of achieving systemic and large-scale structural changes, either through norms, policies, laws or budgets. It results in a shift or influence on gender relations in some way. his info-note addresses how gender transformation relates to the scaling up of gender and social inclusion in climate-resilient agriculture.